2017
DOI: 10.1590/2177-6709.22.6.099-109.sar
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity laser application in Orthodontics

Abstract: Introduction: In dental practice, low-level laser therapy (LLLT) and high-intensity laser therapy (HILT) are mainly used for dental surgery and biostimulation therapy. Within the Orthodontic specialty, while LLLT has been widely used to treat pain associated with orthodontic movement, accelerate bone regeneration after rapid maxillary expansion, and enhance orthodontic tooth movement, HILT, in turn, has been seen as an alternative for addressing soft tissue complications associated to orthodontic treatment. Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 34 publications
0
21
0
7
Order By: Relevance
“…High‐intensity lasers (>10 W) have been gaining traction for medical application, orthodontics pain management, rapid dentin bonding, and tissue ablation in ophthalmic surgeries . Recent development and commercialization of UVA laser diodes are underway (currently prohibitively expensive), but the miniaturization to 5.6 mm diode “TO can” allows a 72 µm spot size at the same intensities described above (70 mW → 17 µW µm −2 ) revealing the advantages and portability of diode‐prototype developments .…”
Section: Comparison Of Energy Generated Per Pulse Versus Required Actmentioning
confidence: 99%
“…High‐intensity lasers (>10 W) have been gaining traction for medical application, orthodontics pain management, rapid dentin bonding, and tissue ablation in ophthalmic surgeries . Recent development and commercialization of UVA laser diodes are underway (currently prohibitively expensive), but the miniaturization to 5.6 mm diode “TO can” allows a 72 µm spot size at the same intensities described above (70 mW → 17 µW µm −2 ) revealing the advantages and portability of diode‐prototype developments .…”
Section: Comparison Of Energy Generated Per Pulse Versus Required Actmentioning
confidence: 99%
“…The diode laser is another alternative for this procedure; however, it can cause the tissue to detach, thus slowing healing. 34 So far, only animal studies using diode lasers for fiberotomy have been found during the retention period after orthodontic treatment. 30 It should be noted that this type of laser is the most widely used in clinical trials to evaluate the effectiveness of fiberotomy, taking into account that it is little absorbed by teeth and bones, making it a safer procedure due to the lower risk of hard tissue damage.…”
Section: Using Laser or Electrosurgerymentioning
confidence: 99%
“…Different types of lasers currently serve as a supplement to or as a replacement for some conventional procedures, such as caries removal [1], gingivectomy, frenectomy, and surgical exposure of teeth. Research in the contemporary orthodontic field opened new horizons in the acceleration of tooth movement, pain control, and bone regeneration, as well as the adhesion of orthodontic brackets and debonding procedures [2].…”
Section: Introductionmentioning
confidence: 99%